When good intentions pave the road to hell: Monetization fears and Europe's narrowing options - Andrea Terzi (Levy Economics Institute of Bard College, 2014)
With the creation of the Economic and Monetary Union and the euro, the national government debt of eurozone member-states became credit sensitive. While the potentially destabilizing impact of adverse cyclical conditions on credit-sensitive debt was seriously underestimated, the design was intentional, framed within a Friedman-Fischer-Buchanan view that "no monetization" rules provide a powerful means to discipline government behavior. While most countries follow some kind of "no monetization" rule, the one embraced by the eurozone was special, as it also prevented monetization on the secondary market for debt. This made all eurozone public debt defaultable - at least until the European Central Bank (ECB) announced the Outright Monetary Transactionsprogram, which can be seen as an enhanced rule-based approach that makes governments solvent on the condition that they balance their budgets. This has further narrowed Europe's options for policy solutions that are conducive to job creation. An approach that would require no immediate changes in the European Union's (EU) political structure would be for the EU to fund "net government spending in the interest of Europe" through the issue of a eurobond backed by the ECB.
Keywords: E63; H63; 330; Euro; Eurozone; Debt Monetization; Sovereign Debt Crisis; Government Budget Constraint